1996
DOI: 10.1111/j.1365-2133.1996.tb06993.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic pseudo-obstruction: a complication of herpes zoster

Abstract: Herpes zoster has been associated rarely with somatic and visceral motor complications, including segmental motor paralysis, neurogenic bladder dysfunction and, unusually, colonic pseudo-obstruction. We report a patient who developed acute pseudo-obstruction of the colon which followed the appearance of dermatomal herpes zoster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Antiviral medication to treat the herpes zoster was prescribed in only 7 of the patients (24%); none of the studies found that the treatment helped to relieve the intestinal pseudo-obstruction. In 2 patients, antiviral medication was prescribed after recovery from the obstruction, and in another 2, including the present patient, the obstruction occurred while that treatment was being given (17,19,22). Our patient is among the 5 (17%) who underwent surgery (7,10,20,22).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Antiviral medication to treat the herpes zoster was prescribed in only 7 of the patients (24%); none of the studies found that the treatment helped to relieve the intestinal pseudo-obstruction. In 2 patients, antiviral medication was prescribed after recovery from the obstruction, and in another 2, including the present patient, the obstruction occurred while that treatment was being given (17,19,22). Our patient is among the 5 (17%) who underwent surgery (7,10,20,22).…”
Section: Discussionmentioning
confidence: 80%
“…The review included 22 male and 7 female patients (24%) aged 32-87 years (mean, 61 years), including the present patient. Significant co-morbidities were present in 45% of the patients and included eight malignancies (28%), immunosuppression for eczema or transplant, human immunodeficiency virus, and arterial hypertension (8,(12)(13)(14)16,18,19,(21)(22)(23)25). The time of skin eruption was variable when compared with the onset of the pseudoobstruction.…”
Section: Discussionmentioning
confidence: 97%
“…Visceral neuropathy and pseudoobstruction of the small and large intestine have been reported as complications of HZ in 19.4% of patients presenting with abdominal pseudohernia [4]. Pseudoobstruction and abdominal distension often develop concurrent with [5] or after the skin rash [33], thus the diagnosis of HZ is achieved early. In the current case abdominal distension, constipation and signs of intestinal obstruction developed one day prior to the appearance of the skin rash.…”
Section: Discussion On Visceral Manifestationsmentioning
confidence: 99%
“…[11][12][13][14][15] Bulges usually fall into one of three general categories: (1) intra-abdominal causes, (2) abdominal wall processes, or (3) neurological disorders.…”
Section: Abdominal Bulgesmentioning
confidence: 99%